Functional characteristics of pluripathological patients going to an urban ambulatory in Lara – Venezuela (Revista Venezolana de Salud Pública, 2021)
In a first study carried out in Venezuela, the frequency and clinical characteristics of pluripathological patients (PP) who attended an urban ambulatory were determined, leaving a gap in terms of functional deterioration. It for this and the absence of regional and national studies on this aspect that the need arose to determine the functional characteristics of these individuals. A cross-sectional descriptive study was performed, with an accidental non-probabilistic sample of 165 patients, over 20 years of age, of both sexes, 40 of them classified as PP according to the diagnostic criteria of the “Junta de Andalucía”. The Barthel Index was applied to the latter. The SPSS statistical package was used. Of the PP, 72.50% were dependent. 40% had moderate dependence; 17.50% scarce and 15% severe. Of the intermediate adults 71.43% had dependence, 35.72% moderate, 28.57% scarce and 7.14% severe. Of the elderly, 73.08% were dependent, moderate in 42.31%, severe in 19.23% and scarce in 11.54%. Regarding the female sex 79.31% dependence, moderate 51.73%; scarce and severe 13.79% each. Of the male sex, 54.55% had dependence, 27.27% low, 18.18% severe and 9.10% moderate. It was observed that the ¾ parts of the PP were dependent, prevailing in older and intermediate adults, with a difference between both of 1.65%, and predominance of moderate deterioration, suggesting that pluripathology could occur in increasingly younger people and with a degree of dependency similar to those of advanced age, alarming to have obtained
Keywords: Barthel index; pluripathological patients